A survey on anomalies detection techniques and measurement methods - Muruti G.; Rahim F.A.; Bin Ibrahim Z.-A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Learning systems; Measurement; Network security; Dynamic researches; Measurement methods; Techniques; Validation; Anomaly detection